Daidzein and genestein contents in tempeh and selected soy products. - Haron, Hasnah; Ismail, Amin; Azlan, Azrina; Shahar, Suzana; Loh, Su Peng (Elsevier Science Limited, 2009)
The total isoflavones in tempeh and selected local soy products was determined. Raw tempeh contained 26 ± 6 mg daidzein (Da) and 28 ± 11 mg genestein (Ge) while fried tempeh contained 35 ± 11 mg Da and 31 ± 11 mg Ge in 100 g (wet basis). Total isoflavone content in 100 g of raw tempeh, based on a dry weight, was 205 ± 56 mg and significantly reduced to 113 ± 41 mg in 100 g of fried tempeh. Tempeh in batter was deep-fried for 30 min which reduced 45% of the total isoflavone content compared to the raw one. Raw tempeh contained the highest total content of isoflavone among the studied local soy products. Total isoflavone content in processed soy foods like egg tofu and home made soybean drink were significantly lower than other soy products studied.